New species of Dryocosmus Giraud gallwasps from California (Hymenoptera: Cynipidae: Cynipini) galling Chrysolepis Hjelmq. (Fagaceae) - Nicholls, James A.; Melika, George; Demartini, John; Stone, Graham N. (Zootaxa, 2018)
Four species of Dryocosmus cynipid gallwasps are now known to induce galls on Chrysolepis in California and Oregon. Two new species, Dryocosmus demartinii Melika, Nicholls & Stone and Dryocosmus juliae Melika, Nicholls & Stone are described. Males of the sexual generation of D. rileypokei plus adults of the asexual generation of this species are both described for the first time. A detailed description of D. castanopsidis is given for the first time. In addition to descriptions we provide diagnoses and information on biology and host associations for all four species. All the newly described taxa are supported by morphological and molecular data.